2019
DOI: 10.3390/rs11212569
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Quiet Solar Luminosity Variability from TSI Satellite Measurements and Proxy Models during 1980–2018

Abstract: A continuous record of direct total solar irradiance (TSI) observations began with a series of satellite experiments in 1978. This record requires comparisons of overlapping satellite observations with adequate relative precisions to provide useful long term TSI trend information. Herein we briefly review the active cavity radiometer irradiance monitor physikalisch-meteorologisches observatorium davos (ACRIM-PMOD) TSI composite controversy regarding how the total solar irradiance (TSI) has evolved since 1978 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 70 publications
(300 reference statements)
1
52
0
Order By: Relevance
“…It has been pointed out that because the TSI models do not contain any allowance for changes in the quiet Sun component, taking the difference between the models and the observations can provide evidence of long term changes in the quiet Sun component (Scafetta et al, 2019). Some journal papers have postulated quiet-Sun variations to generate TSI reconstructions that have much larger long-term variations (e.g.…”
Section: III Long Term Variations Of the Quiet Sunmentioning
confidence: 99%
“…It has been pointed out that because the TSI models do not contain any allowance for changes in the quiet Sun component, taking the difference between the models and the observations can provide evidence of long term changes in the quiet Sun component (Scafetta et al, 2019). Some journal papers have postulated quiet-Sun variations to generate TSI reconstructions that have much larger long-term variations (e.g.…”
Section: III Long Term Variations Of the Quiet Sunmentioning
confidence: 99%
“…Besides the hypothesis of a solar irradiance forcing modulated by the planets (e.g., Scafetta, 2010Scafetta, , 2012aScafetta, , 2012bScafetta & Willson, 2013a, 2013b, 2014Scafetta, Willson, et al, 2019), several authors also proposed a corpuscular forcing of the climate. For example, Svensmark et al (2009) and Svensmark et al (2017) suggested that the incoming cosmic ray flux could directly modulate the cloud system.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the hypothesis of a solar irradiance forcing modulated by the planets (e.g., Scafetta, 2010, 2012a, 2012b; Scafetta & Willson, 2013a, 2013b, 2014; Scafetta, Willson, et al., 2019), several authors also proposed a corpuscular forcing of the climate. For example, Svensmark et al.…”
Section: Introductionmentioning
confidence: 99%
“…The peaks at 1750, 1850 and 1950 are well correlated, but the minima are not as deep and flat in the TSI-series as in the BIE-observations. In the Hoyt-Schatten-ACRIM reconstruction [69] (lower panel), the peaks fit better and the minima around 1800, 1900 and 1960 are better reproduced. In both TSI reconstructions the BIE position is too far north after 2000 CE.…”
Section: Bie and Tsi Correlationsmentioning
confidence: 98%